2020
DOI: 10.3390/ijerph17165870
|View full text |Cite
|
Sign up to set email alerts
|

Excessive Weight Gain and Dental Caries Experience among Children Affected by ADHD

Abstract: In recent years, attention has been paid to the co-occurrence of attention deficit hyperactivity disorder (ADHD) and obesity, but results in relation to dental caries outcomes differ. The study was conducted to determine obesity/overweight and dental caries in children suffering from ADHD and to draw comparisons with non-ADHD children. A total of 119 children under 11 years old (8.2 ± 1.2) were enrolled into a cross-sectional study: those with confirmed ADHD (n = 39), and healthy controls (n = 80). The behavio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 46 publications
1
18
0
2
Order By: Relevance
“…High prevalence of dental caries (59.3 %) with mean DMFT/dmft of 1.71 ± 2.42 / 2.22 ± 3.23 were noted. Further, caregiver’s education level of less than 8 years was found to be associated with dental caries experience using a Poisson Regression model [PR = 1.439 (1.09–1.89)] Conclusion: CP patients demonstrated high caries prevalence and association with fewer education years of caregivers Attention Deficit Hyperactivity Disorder (ADHD) Paszynska et al [ 81 ] Determine prevalence of obesity/overweight (BMI) and dental caries (ICDAS) in children (under 11 years of age) with attention deficit hyperactivity disorder (ADHD) and compare with non-ADHD control group. Behavioral evaluation and parent interview for food habits was also conducted Case-control 119 (39 cases and 80 controls) Poland Outcomes: ADHD group had significantly higher BMI compared to controls (p = 0.016).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…High prevalence of dental caries (59.3 %) with mean DMFT/dmft of 1.71 ± 2.42 / 2.22 ± 3.23 were noted. Further, caregiver’s education level of less than 8 years was found to be associated with dental caries experience using a Poisson Regression model [PR = 1.439 (1.09–1.89)] Conclusion: CP patients demonstrated high caries prevalence and association with fewer education years of caregivers Attention Deficit Hyperactivity Disorder (ADHD) Paszynska et al [ 81 ] Determine prevalence of obesity/overweight (BMI) and dental caries (ICDAS) in children (under 11 years of age) with attention deficit hyperactivity disorder (ADHD) and compare with non-ADHD control group. Behavioral evaluation and parent interview for food habits was also conducted Case-control 119 (39 cases and 80 controls) Poland Outcomes: ADHD group had significantly higher BMI compared to controls (p = 0.016).…”
Section: Resultsmentioning
confidence: 99%
“…In a case-control study of participants with ADHD, Paszynska et al found significantly higher BMI in test group and significantly higher ICDAS 5 and 6 scores (teeth with advanced caries) in the primary dentition. They also found that increased intake of sugary foods and drinks were significantly higher in ADHD group[ 81 ]. It appears that in studies determining associations of dental caries with neurological and behavioral disorders, standardized interviews for caretakers, food habits and other social determinants will be crucial in order to draw informed conclusions and not extrapolate mechanistic links between systemic diseases and dental caries.…”
Section: Discussionmentioning
confidence: 99%
“…Their concentrations in saliva are essential also for stimulating dental caries development in the oral cavity. Our previous study showed high dental caries in primary and permanent dentition among ADHD children [ 58 ]. Additionally, tooth decay was related to sweetened drink intake [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study showed high dental caries in primary and permanent dentition among ADHD children [ 58 ]. Additionally, tooth decay was related to sweetened drink intake [ 58 ]. Therefore, alpha-amylase and immune biomarkers may both be at an enhanced level, and further research is necessary to link oral homeostasis and ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the literature review on childhood obesity, cause-and-effect relationships to oral diseases show strong associations with periodontal diseases and different relationships to caries progression, such as confirming [24][25][26] or denying [27][28][29][30]. It seems to depend on multiple factors contributing to the disease progress and the risk of dental caries in primary and permanent dentition among pediatric patients affected by simple obesity.…”
Section: Dental Cariesmentioning
confidence: 99%